A feasibility study of a small-scale photovoltaic-powered reverse osmosis desalination plant for potable water and salt production in Madura Island: A techno-economic evaluation. (1st October 2022) - Ayou, Dereje S.; Ega, Habibie Muhammad; Coronas, Alberto
Highlights: Techno-economic analysis of a small-scale PV-RO desalination plant in Madura Island. Potable water production of 11.6 m 3 /day with an annual solar contribution of 84 % The levelized cost of water production using PV-RO desalination plant is 9.0 USD/m 3. Payback period of PV-RO plant is 4 years for plant lifetime of 25 years. PV-RO plant usage can increase salt production effectiveness of the salt farmers. Abstract: The use of reverse osmosis (RO) desalination plant powered by a photovoltaic (PV) system is an attractive solution for small-scale applications in Madura Island (Indonesia). In this paper, the techno-economic feasibility of a small-scale grid-connected PV-RO desalination plant has been carried out in Madura Island for a plant capacity of 11.6 m 3 /day. The RO brine concentrate is utilized for valuable salt production-via-evaporation ponds that allowed the reduction of the required size in the conventional salt evaporation ponds. The steady-state numerical model of the RO desalination plant was used to predict the plant's performance using the characteristics of commercial RO elements. The PV array simulation was carried out using a dynamic modelling and simulation program based on weather data of Madura Island. The result illustrates that the production of potable water and salt using a community-scale grid-connected PV-RO plant is economically viable to be implemented in the region. The payback period of this PV-RO plant is around 4 years for a considered plant lifetime of 25 years with an annual solar contribution of 84 %. The Levelized cost of water production using the PV-RO plant is about 9.0 USD/m 3 which is more cost-effective than the current cost of potable water in the region. Besides, the use of solar-assisted RO desalination plants in water-stressed regions such as Madura Island allows for mitigating the greenhouse gas emissions associated with seawater desalination.